Early Tibetan mandalas : the Rossi collection - Singer, Jane Casey (2003)
[Dt.:] In dieser Ausstellung werden 14 verschiedene Mandalas gezeigt, die alle zwischen dem 13. und dem 16. Jahrhundert entstanden sind. Sie stammen aus der Sammlung von Anna Maria und Fabio Rossi (Rossi Collection). Neben den Abbildungen der einzelnen Mandalas steht auch ein Ausstellungskatalog zur Verfügung, der von Jane Casey Singer verfasst wurde. - [Engl.:] This online exhibition features 14 fine Tibetan paintings of mandalas dating from the thirtennth to the sixteenth centuries, drawn from the collections of Rossi & Rossi, London. The website includes also an exhibition catalogue. The text of the catalogue was written by Jane Casey Singer and digitized by Gisella Minke Lhalungpa.